3D Printing Technology in Dentistry: A Review - Dr. H. L Gupta,; Dr. Sumit Bhatt,; Dr. Yash Rajendra Shaha,; Dr. Mona J Shah,; Dr. Shubham Gupta,; Dr. Amruth N Petkar, (The Bioscan, 2025)
3D printing technology has revolutionized various industries, and dentistry is no exception. This review explores the integration of 3D printing in dental applications, focusing on its impact on the precision of dental restorations, the efficiency of orthodontic treatments, and the overall patient experience. By examining recent advancements, the types of materials used, and the implications for workflow optimization, this review highlights the transformative potential of 3D printing in enhancing dental practices. The findings suggest that 3D printing not only improves clinical outcomes but also offers cost-effective solutions in patient care.